Organizational conditions for engagement in quality and safety improvement: a longitudinal qualitative study of community pharmacies - Denham L. Phipps; Christian E. L. Jones; Dianne Parker; Darren M. Ashcroft (BMC, 2018)
Abstract Background While efforts have been made to bring about quality and safety improvement in healthcare, it remains by no means certain that an improvement project will succeed. This suggests a need to better understand the process and conditions of improvement. The current study addresses this question by examining English community pharmacies attempting to undertake improvement activities. Method The study used a longitudinal qualitative design, involving a sample of ten community pharmacies. Each pharmacy took part in a series of improvement workshops, involving use of the Manchester Patient Safety Framework (MaPSaF), over a twelve-month period. Qualitative data were collected from the workshops, from follow-up focus groups and from field notes. Template analysis was used to identify themes in the data. Results The progress made by pharmacies in improving their practice can be described in terms of a behavioural change framework, consisting of contemplation (resolving to make changes if they are required), planning (deciding how to carry out change) and execution (carrying out and reflecting on change). Organizational conditions supporting change were identified; these included the prioritisation of improvement, a commitment to change, a trusting and collaborative relationship between staff and managers, and knowledge about quality and safety issues to work on. Conclusions Our study suggests a process by which healthcare work units might undergo improvement. In addition to recognising and providing support for this process, it is important to establish an environment that fosters improvement, and for work units to ensure that they are prepared for undergoing improvement activities.